KADAR ANTOSIANIN DAN AKTIVITAS ANTIOKSIDAN FLAKE BERAS MERAH DAN BERAS KETAN HITAM DENGAN VARIASI SUHU PEREBUSAN - Setiawati, Hany; Marsono, Yustinus; Sutedja, Anita Maya (Widya Mandala Surabaya Catholic University, 2013)
Red rice and black glutinous rice contain high starch and satiety thus suitable for use as raw material for produce breakfast cereal flakes.Anthocyanin compounds found in red rice and black glutinous rice flakes can be damaged during the process. Stage of making a flake that can reduce levels of anthocyanins of red and black glutinous rice is boiling and drying. The design of the study is a randomized block design nested pattern, consisting of two factors. The first factor is the type of rice (the nest) namely red rice (M) and black glutinous rice (H). The second factor is boiling temperature (which is nested) are T1 (70°C), T2 (80°C) and T3 (90°C). Parameters tested the levels of anthocyanin content, total phenolic content and antioxidant activity. The data obtained were subsequently analyzed by ANOVA at α = 5%. If there is a real effect, then continued with LSD test with α = 5%. The test results showed that the difference in boiling temperatures is caused a decrease in the levels of anthocyanin black glutinous rice flake, total phenolic content of red rice flakes and black glutinous rice and ferric reducing capacity of red rice and black rice flakes. The difference in boiling temperature had no significant effect on levels of anthocyanin of red rice flakes and radical DPPH scavenging activity of red rice and black glutinous rice flakes. The best treatment are flake with 80°C boiling temperature (T1). Red and black glutinous rice flake with T1 treatment has anthocyanin content are 5,9±1,5 and 211,8±22,2 μg/g, total phenolic are 291,8±15,0 and 488,3±8,4 μg/g, ferric reducing activity are 3,9±0,1 and 4,9±0,3 mg/g and radical scavenging activity are 49,51±2,14% dan 46,73±1,44%.